2011
DOI: 10.1002/j.2161-0045.2011.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselors' Perspectives on Using the Career Style Interview With Clients

Abstract: The authors investigated counselors' perspectives on using the Career Style Interview (CSI) with clients who had career concerns. Participants were a purposive sample of 34 counselors who had been trained in and who had used the CSI with clients. The findings indicated that the counselors viewed the CSI as a helpful and positive career counseling intervention. It was most effective at identifying clients' life themes and assisted them with making meaningful career decisions. Implications of these findings for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Budding research on the CCI indicates encouraging results. Rehfuss, Cosio, and Del Corso (2011) evaluated use of the CCI with practicing counselors (N = 34), who stated they found the CCI helpful in working with career clients. Additionally, Rehfuss, Del Corso, Galvin, and Wykes (2011) noted that clients moved toward more specificity in career types (Holland coding recall) after a CCI.…”
Section: Methodsmentioning
confidence: 99%
“…Budding research on the CCI indicates encouraging results. Rehfuss, Cosio, and Del Corso (2011) evaluated use of the CCI with practicing counselors (N = 34), who stated they found the CCI helpful in working with career clients. Additionally, Rehfuss, Del Corso, Galvin, and Wykes (2011) noted that clients moved toward more specificity in career types (Holland coding recall) after a CCI.…”
Section: Methodsmentioning
confidence: 99%
“…There are only a few research studies on CCC, including some outcome studies on individual (Refhuss, Del Corso, Glavin, & Wykes, 2011) and group counseling (Di Fabio & Maree, 2011), as well as a study that is focused on the counselor's perspective on the intervention (Refhuss, Cosio, & Del Corso, 2011). These studies support CCC efficacy in career counseling.…”
mentioning
confidence: 99%
“…The effectiveness of the CCI in these case study demonstrations underscores the usefulness of narrative interventions in helping people to create meaningful occupational futures (Bujold, 2004). Another qualitative study examined the usefulness of the CCI as a career counselling technique from the perspective of 34 counsellors trained in conducting the interview (Rehfuss, Cosio, & Del Corso, 2011). A qualitative study with 18 client-counsellor dyads using the CCI reported that, as a result of the intervention, clients attained greater career awareness, self-confidence, sense of direction, and confirmation that they were on the right career path (Rehfuss, Del Corso, Glavin, & Wykes, 2011).…”
Section: Empirical Supportmentioning
confidence: 99%